ANALISIS TINDAK TUTUR DIREKTIF DALAM PEMBELAJARAN DI KELAS V SDN 278 PALATTAE KECAMATAN KAHU KABUPATEN BONE - Mega, Lesta; Rohana, Rohana; Irfan, Muhammad; Zainuddin, M. Said (Universitas Borneo Tarakan, 2023)
This study aims to describe the types and functions of directive speech acts in learning in class V SDN 278 Palattae, Kahu sub-district, Bone district. This research is descriptive qualitative research. The techniques used in collecting data are observation techniques and documentation techniques. Data analysis used a pragmatic pairing technique. Determining the types and functions of directive speech acts in learning is based on indicators of types and functions of directive speech acts derived from Ibrahim's theory. The results of research on learning in class V of SDN 278 Palattae, Kahu sub-district, Bone district show that the use of the type of question and the function of asking is more widely used when compared to the use of other types and functions of directive speech acts. It can be seen in the description of the research results, which show that the type of question with the function of asking is dominant. The types of directive speech acts include requests, questions, orders, prohibitions, giving permission, and advice. The functions of directive speech acts found include: requesting, pleading, praying, asking, interrogating, instructing, requiring, demanding, directing, requiring, prohibiting, restricting, approving, granting, forgiving, allowing, suggesting, advising, requesting, and demanding, requesting and directing, inviting and praying, directing and asking, directing and demanding, directing and advising, and finally allowing and suggesting. The most prominent directive speech acts and functions of directive speech acts are questioning and asking